2005
DOI: 10.1007/s11274-004-2889-6
|View full text |Cite
|
Sign up to set email alerts
|

Production of single cell protein through fermentation of a perennial grass grown on saline lands with Cellulomonas biazotea

Abstract: Microbial protein from alkali-treated Leptochloa fusca (kaller grass) was produced by growing Cellulomonas biazotea in shake flasks and in an aerated 6-l fermentor. Single cell protein, produced in the fermentor contained 56.10 ± 4.64, 60.00 ± 5.04, 11.50 ± 1.34, 12.95 ± 1.24, 3.50 ± 0.24 and 1.00 ± 0.44% true protein, crude protein, crude fibre, ash, cellulose and RNA content respectively. Maximum values compared favourably with published data. The biomass contained all desired amino acids with isoleucine as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
1
7
1
Order By: Relevance
“…Data showed that the maximum yield of protein was achieved by the addition of organic nitrogen source as Yeast extract to the production medium. The protein reached after supplementing of yeast extract was higher than the value found by Gao et al (2007) in yeast (53%) and similar with value of Rajoka et al (2006) in C. utilis (56.34%) and yet lower than that found by Rajoka (2005) in Cellulomonas biazotea (60%) and Somda et al (2017) in Saccharomyces cerevisiae SKM10 (79.14%). The mean values of lipids content significantly ranged (p<0.01) from 4.64±0.35 to 13.25±0.11% (w/w).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Data showed that the maximum yield of protein was achieved by the addition of organic nitrogen source as Yeast extract to the production medium. The protein reached after supplementing of yeast extract was higher than the value found by Gao et al (2007) in yeast (53%) and similar with value of Rajoka et al (2006) in C. utilis (56.34%) and yet lower than that found by Rajoka (2005) in Cellulomonas biazotea (60%) and Somda et al (2017) in Saccharomyces cerevisiae SKM10 (79.14%). The mean values of lipids content significantly ranged (p<0.01) from 4.64±0.35 to 13.25±0.11% (w/w).…”
Section: Resultssupporting
confidence: 72%
“…Concerning carbohydrates content, it was found significantly different (p<0.01) and ranged from 1.14±0.10 to 3.80±0.10% (w/w), which are lower to the percentage obtained in Hansenula species (24%) by Shojaosadati et al (1999) and S. cerevisiae (26%) by Husseiny et al (2016). Nucleic acid contents of SCP was found to range from 3.33±0.17 to 6.60±0.25% (w/w) which is significantly lower than the values reported by Kurbanoglu (2001) as 7.47% and higher than Ibrahim Rajoka et al (2005) at 2.75%. On the other hand, the high RNA contents are reported to be toxic for human consumption, while harmless for most animals (Kurbanoglu, 2001).…”
Section: Resultscontrasting
confidence: 69%
“…Significant increases in protein content by yeast have been found by Ziino et al (1999). Rajoka (2005) also recorded 60 % crude protein by Candida utilis. Gao et al (2007) showed that, the content of protein in marine yeast reached 53%.…”
Section: Analytical Characterization Of Yeast Biomass Single Cell Promentioning
confidence: 89%
“…Micro-organisms have the ability to upgrade low protein plant material to high protein feed via fermentation [7]. Fermentation enhances the nutrient content of foods through the biosynthesis of proteins, vitamins and essential amino acids.…”
Section: Introductionmentioning
confidence: 99%